Contextual Teaching and Learning-Based Module to Improve Social Studies Learning Outcomes of Fourth Grade Elementary School Students - Riski Ayu Lestari; Yadri Irwansyah; Tio Gusti Satria; Asep Sukenda Egok (EDUJAVARE: International Journal of Educational Research, 2026)
Education has a very important role in forming quality human resources and able to adapt to the times, especially in the 21st century era. This study aims to develop a contextual-based social studies teaching module that is valid, practical, and effective in improving the learning outcomes of fourth-grade students at SD Negeri Bina Karya. This research is a Reserch and Development (R&D) study using the ADDIE model, which consists of analysis, design, developent, implementation, and evaluation stages. The subject od this study were 26 fourth-grade students of SD Negeri Bina Karya. Data were collected using vaidation questionnaires, practicality questionnaires, and learning outcome tests in the form of pretest and posttest. The data were analyzed using descriptive quantitative methods. The results showhed that the developed teaching module has a high level of validity, with score of 0,96 from the language expert, 0,94 from the media expert, and 0,96 from the categorized as very valid. The practicality with a score of 93% (very practical), individual trials with 73% and small group of 79% (practical). The effectiveness level was indicated by the improvement of students’ learning outcomes, with an average pretest score of 30% and posttest score od 79% and an N-gain score 0,71 categorized as high. Based on these result, it can be concluded that the cobtextual-based social studies teaching module is valid, practical, and effective for use in the learning process.